PENGADILAN HAK ASASI MANUSIA DARI SUDUT PANDANG PENYELESAIAN KASUS DAN KELEMAHANNYA - Laurensius Arliman S (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2017)
Settlement of human rights violations in Indonesia is regulated in Law Number 26 Year 2000 on Human Rights Court. Any person or group who has reason to believe that their fundamental rights have been violated can file reports and oral or written complaint to the national commission for human rights. This law contains provisions on the establishment of a special human rights court (ad-hoc) to prosecute human rights violations in the past that happened before the law goes into effect, while the permanent human rights court handles only crimes committed after ratification enactment these laws. However, the ad-hoc court as it was only set up to adjudicate pecific cases and formed through a special procedure anyway. The President can only establish ad-hoc courts like this if there is an explicit recommendation of the House of Representatives. Weaknesses in the settlement of human rights violations in Indonesia based on Law Court of human rights within the general judicial system, making it highly dependent on bureaucracy and administration of the public courts occupy, no article that mischaracterized that would allow actors to be free, and also the presence of an age limit whether it is to be investigators, prosecutors, and judges ad-hoc, thus inhibiting the influx of people who are competent.